Pengaruh Aktivitas Rantai Nilai Terhadap Keunggulan Bersaing Pada Perusahaan Pengekspor Coklat di Kota Palu - Wirasakti, Zulkifli (TEMA, 2008)
This Research is aim to know the influence of activity of industry value chain that consist of structural activity, activity procedural, and operational activity, to excellence compete brown exporter company in Palu. This research is using path analysis methods. Research Result indicates that activity of industry value chain that consist of structural activity, activity procedural, and operational activity has an effect on significant to excellence compete company brown exporter, can be shown by coefficient determination as high as 0,801 or 80,1 percents. Activity Variable structural haves dominant influence as high as 0,410 or 41% to excellence compete. Whereas dominant indirect influence is relation/link between structural activity variable and variable of operational activity is 0,109 or 10,9% to excellence compete company brown exporter in Palu. Research result is suggested to company brown exporter to improves structural activity intensity. Nevertheless not overrule operational activity and activity procedural, because the three of this activity each other equips or haves interrelationship (causal). Keywords: Structural, procedural, operational activity, Competitive advantage.